Citric Acid Production: Raw Material, Microbial Production, Fermentation Strategy and Global Market: Critical Review - Abd Alsaheb, Ramzi A.; Mohammed, Malik Mustafa; Abdullah, Jaafar Kamil; Abbas, Azza Hashim (Al-Khwarizmi Engineering Journal, 2023)
Citric acid is an essential ingredient for the manufacture of (12) key industrial chemicals. Citric acid use is increasing steadily with a high annual growth rate as a result of the development of ever more sophisticated applications. Citric acid is widely utilized in the food and pharmaceutical industries due to its low toxicity when compared to other acidulous. Other uses for citric acid can be found in cleaning supplies and detergents. Based on information from a review of the literature, Citric acid production substrates and methods for surface fermentation, submerged fermentation, solid-state fermentation, and international market expansion are all covered in the current review study. Finally, there is still much to learn about the circumstances of the production of citric acid from raw materials, microorganisms, and fermentation techniques to achieve the best production in terms of cost and quality.